A PARADIGM SHIFT IN ECONOMICS OF HINDI FEATURE FILMS. (A CHANGING PRACTICES IN FILM FINANCE IN INDIA) - Oak, Amit Padmakar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Indian film industry is considered to be the largest film industry in the world in terms of number of films produced and released every year. Spread across more than 800 films, cumulative consumer spending on the Indian filmed entertainment products is estimated to be in excess of INR 60 bn every year. The Hindi film industry attracts 40-50% of total consumer spending on Indian filmed entertainment products (Sunir Khetrapal report on Film financing 2008).